2021
DOI: 10.1007/s12072-021-10158-x
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir/velpatasvir for patients with chronic hepatitis C virus infection and compensated liver disease: real-world data in Taiwan

Abstract: Background Data regarding the real-world effectiveness and safety of sofosbuvir/velpatasvir (SOF/VEL) for East Asian patients with chronic hepatitis C virus (HCV) infection and compensated liver disease are limited. We evaluated the performance of SOF/VEL for 12 weeks for HCV-infected patients with compensated liver disease in a large real-world cohort in Taiwan. Methods Between July 2019 and March 2020, 1,880 HCV-infected patients with compensated liver disease who received SOF/VEL 400/100 mg once daily for 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…Although there have been some real-world analyses on the use of SOF/VEL in Taiwan published recently, there is still a gap in data available. The studies that have been published to date have reported high SVR12 rates (between 98% and 100%) [ 19 , 21 ]. A study using the TACR database previously investigated the efficacy of SOF/VEL, reporting SVR12 rates of 99%.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been some real-world analyses on the use of SOF/VEL in Taiwan published recently, there is still a gap in data available. The studies that have been published to date have reported high SVR12 rates (between 98% and 100%) [ 19 , 21 ]. A study using the TACR database previously investigated the efficacy of SOF/VEL, reporting SVR12 rates of 99%.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, data are not available concerning the screening and treatment rates for HCV among HIV-positive MSM patients in Taiwan. Studies have shown that the SVR 12 rates in HIV-positive patients in Taiwan with pangenotypic sofosbuvir/velpatasvir (SOF/VEL) and glecaprevir/pibrentasvir (GLE/PIB) range from 97.1% to 98.2% and are comparable to the response rates in the usual population [ 39 , 41 , 42 ]. By increasing patient awareness, mass screening, point-of-care testing, and link-to-care programs, the HCV reservoir in at-risk populations could be efficiently controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, studies before 2005 universally demonstrated a very low prevalence of HCV genotype 6 in the general population [ 31 , 32 ]. After the outbreak of HIV and HCV among IDUs in 2005, studies have shown that the seroprevalence of HCV genotype 6 had increased to 5%–10% in the general population [ 33 , 34 ]. In terms of PLWH, the prevalence of HCV genotype 6 was around 20%–30%, which also was likely associated with IDUs who had HIV coinfection [ 35–37 ].…”
Section: Discussionmentioning
confidence: 99%